Penerapan Model Pembelajaran Project-Based Learning pada Pembelajaran IPA untuk Meningkatkan Nilai Conviction, Creativity dan Community - L.Eny Listyarini (UNIB Press, 2023)
Creativity and Community are important to be developed in learning at school. The three values of Tarakanita in class VIIC of SMP Tarakanita 2 Jakarta are still not developed. One of the learning models that can be applied to increase Conviction, Creativity and Community is Project Based Learning. This research aims to implement Project Based Learning with the aid of a module to improve Conviction, Creativity, and Community for class VII students of SMP Tarakanita 2 Jakarta on environmental pollution. The research method used is Classroom Action Research which consists of three cycles. Every cycles consist of three stages, they are planning, observation, action and reflection. The research subject is class VIIC SMP Tarakanita 2 Jakarta as many as 29 students. The research instrument used to obtain the data is the rubric for assessing conviction, creativity and community. Assessment with the rubric is carried out during the learning activities. The rubric used to measure the conviction value consists of five indicators, creativity consists of four indicators and community consists of four indicators. The results showed that there was an increase in conviction, creativity and community. The average value of conviction in cycle one is 50.8, in cycle two is 77.0 and in cycle three is 91.1. The average value for creativity ability in cycle one is 50.0 in cycle two is 77.6 and in cycle three is 92.5. The average value of the community in the first cycle is 48.0, in the second cycle 77.6 and in the third cycle 93.1. From these results, it can be concluded that the implementation of Project Based Learning with the help of modules on Environmental Pollution material in Class VII SMP Tarakanita 2 Jakarta can increase Conviction with an N-Gain value of 0.9 (high), Creativity with an N-Gain value of 0.8 (high). and Community with an N-Gain value of 0.9 (high).